Relationship between three dietary indices and health-related quality of life among rural elderly in China: a cross-sectional study - Yang, Chen; Liu, Peijun; Huang, Wenjing; Zhou, Ying; Liu, Cuiping; Gao, Tianlin; Zhong, Feng (Frontiers in Nutrition, 2023)
Purpose This study aimed to explore the association between health-related quality of life (HRQOL) and diet quality using three evidence-based dietary indices among older people in rural China. Methods This cross-sectional study included 1258 rural older people (mean age 72.32 years; 55.6% female). HRQOL was assessed using the European Five Dimension Health Scale (EQ-5D), and dietary intake was assessed using a Food Frequency Questionnaire. Three dietary scoring indices, including the Alternate Healthy Eating Index, Dietary Approaches to Stop Hypertension, and Dietary Diversity Score (DDS), were calculated to assess and analyze the relationship between these dietary indices and quality of life. Results The EQ-5D score was 0.95±0.10, and the EQ-Visual Analog Scale (VAS) score was 76.76±14.44. All three groups with higher dietary indices had higher quality of life scores. After controlling for covariates in multivariate adjusted binary logistic regression analyses, participants in the top tertile of DDS had higher quality of life scores than those in the bottom tertile. DDS was consistently associated with EQ-5D (Model2: OR=1.567,p=0.001; Model3: OR=1.351, p=0.044) and EQ-VAS (Model2: OR=1.830, p＜0.001; Model3: OR=1.383, p=0.047), significantly different from the other groups. Conclusion Older people in rural China who adhere to various foods experience a better quality of healthy life.